Building the identity of the student in the face of the gender ideology bill/A construção da identidade do aluno frente ao projeto lei de ideologia de gênero - Maiara Cristine Oliveira de Almeida; Carolina Sena do Vale; Cristiano Cezar Gomes da Silva (Universidade Estadual de Alagoas, 2020)
The present work brings a brief discussion about the concepts of ideology, gender and identity from the debate about the student's identity against the gender ideology bill. In the course of the work, such concepts were correlated to the gender ideology law project with the student's identity construction. Authors were mobilized, such as: Althusser (1995), Arroyo (2004), Carvalho (2011), Foucault (1988), Hall (2005), Louro (2007), Souza e Silva (2018) e Silva (2017) , in addition to some legal rules. From the methodological point of view, bibliographical analyzes were performed to, from the readings, bring elements to the present discussion. It is noteworthy that the school must enable the development of critical thinking from the understanding of the body and sexual differences that are culturally built in society, having a fundamental role in the demystification of these differences, besides being an important instrument in the construction of values and attitudes. that allow a more critical and reflective look at gender and sexual identities. In this sense, this work aims to arouse debate and reflection on gender ideology in the construction of identity from the school.